Students’ Critical Thinking Skills on Algebraic Problems Through Mathematical Resilience - Faradillah, Ayu; Humaira, Tia (Jurnal Pendidikan Indonesia, 2022)
Mathematics has an important role in carrying out everyday life and in other sciences because mathematics can involve many things. This study aims to analyze students’ critical thinking skills through mathematical resilience. This study used a descriptive qualitative method. The number of subjects of this study were 473 Senior High School students from 6 different schools, in which the process of selecting the subject used Winstep. The research instruments were questionnaires, test and interviews. The analysis in this study is seen from two aspects, namely school and gender. To find out the students' responses to the questionnaire that had been distributed, the researcher used the Rasch Model which was then exported into an excel file. After that, the data were analyzed using Winstep software. The result of this research was that mathematical resilience had no effect on critical thinking skills. It was proven in this study that students with high mathematical resilience turned out to have low critical thinking skills, students with medium mathematical resilience had high critical thinking skills, and students with low mathematical resilience had medium critical thinking skills.